FEATURES OF ARTISTIC EXPRESSION OF MYTHOLOGICAL CHARACTERS IN THE POEMS OF FARZONA KHOJANDI (Scientific journal of the Fergana State University, 2023)
This article discusses the features of the artistic expressiveness of mythological characters in the poems of the national poet of Tajikistan Farzonai Khojandi. The main goal was to explore the poet's new interpretation of mythological characters with poetic art and craftsmanship.